Effect of planting time, spacing and pinching on growth and seed yield traits in African marigold (Tagetes erecta) cv. Pusa Narangi Gainda - MEENA, YADRAM; SIROHI, H S; TOMAR, B S; KUMAR, SANJAY (The Indian Journal of Agricultural Sciences, 2015)
The present investigation was carried out at the Horticulture Farm, Chaudhary Chhotu Ram (PG) College, Muzaffarnagar, UP, for consecutive two years to study the effect of planting time, spacing and pinching on plant growth and seed yield characters in African marifold (Targets exeta L.). It was noted that planting time, wider spacing and pinching at 60 DAT had significant effect on number of days to first flowering and number of flowers/plant. The higher plant height was recorded in September planting, 30 cm × 30 cm spacing and in without pinching treatments. The number of branch/plant and diameter of main stem were higher in October planting, 30 cm × 60 cm spacing (19.87) but pinching at 30 DAT had produced maximum diameter of stem (1.36 cm) than others.The maximum seed yield/flower (0.58 g), seed yield/plant (17.82 g) and seed yield/plot (254.44g) were recorded in September planting while closer spacing 30 cm × 30 cm had given higher seed yield/flower (0.60g), seed yield/plant (17.71g) and seed yield/plot (262.28g). The pinching at 60 DAT has given higher seed yield/ flower (0.55g), seed yield/plant (19.01g), seed yield/plot (283.61g) followed by pinching at 30 DAT. Significant interaction between time of planting × spacing, pinching × spacing, time of planting × spacing × pinching were recorded for seed yield/flower and the interaction between pinching × time of planting was recorded significant for seed yield/plot.